2(2x+3)-7x=-5(x+3x)

Simple and best practice solution for 2(2x+3)-7x=-5(x+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+3)-7x=-5(x+3x) equation:


Simplifying
2(2x + 3) + -7x = -5(x + 3x)

Reorder the terms:
2(3 + 2x) + -7x = -5(x + 3x)
(3 * 2 + 2x * 2) + -7x = -5(x + 3x)
(6 + 4x) + -7x = -5(x + 3x)

Combine like terms: 4x + -7x = -3x
6 + -3x = -5(x + 3x)

Combine like terms: x + 3x = 4x
6 + -3x = -5(4x)

Remove parenthesis around (4x)
6 + -3x = -5 * 4x

Multiply -5 * 4
6 + -3x = -20x

Solving
6 + -3x = -20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20x' to each side of the equation.
6 + -3x + 20x = -20x + 20x

Combine like terms: -3x + 20x = 17x
6 + 17x = -20x + 20x

Combine like terms: -20x + 20x = 0
6 + 17x = 0

Add '-6' to each side of the equation.
6 + -6 + 17x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 17x = 0 + -6
17x = 0 + -6

Combine like terms: 0 + -6 = -6
17x = -6

Divide each side by '17'.
x = -0.3529411765

Simplifying
x = -0.3529411765

See similar equations:

| (x+4)(x-12)-5x=0 | | 9*2x=10(x+8) | | 112=4+96x-16x^2 | | 4x-4=-46-3x | | 6(a1/2)-7 | | 5x-2(3x+4)=-20 | | 6.8c+5=25.4 | | 14x/21y | | 6.8c+5=25.5 | | (5x-30)^-4/3 | | 15m-6m=18 | | 10b-2b+2+b-4b= | | 4x+15=15x-62 | | 5x-2(3x+4)=-12 | | 1-2+1-6+1-10= | | 14k-7k=14 | | 5x/72=5/8 | | 10x+25y+5= | | 1/7=8 | | 14m+8=5m-28 | | 5/11÷-30/11 | | 5j-4j=15 | | 6/10=/5 | | =16x^3+12x^2+8x | | 22/30 | | 4(r-3)= | | 15x^6-13x^5+17x^4= | | x+(x+1)=60 | | =16x^3+12x^2+8 | | (3z/8)-4=5 | | 6x+1=x+61 | | 7x+x=-16 |

Equations solver categories